2010
DOI: 10.1186/1472-6963-10-117
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of HIV prevention interventions in Andhra Pradesh state of India

Abstract: BackgroundInformation on cost-effectiveness of the range of HIV prevention interventions is a useful contributor to decisions on the best use of resources to prevent HIV. We conducted this assessment for the state of Andhra Pradesh that has the highest HIV burden in India.MethodsBased on data from a representative sample of 128 public-funded HIV prevention programs of 14 types in Andhra Pradesh, we have recently reported the number of HIV infections averted by each type of HIV prevention intervention and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Most studies evaluated a package of prevention or prevention and treatment interventions and around a third of the interventions integrated to the current health care system or programs on the ground (Additional file 3 ). For example, Dandona et al [ 35 ], evaluated a program consist of behaviour change, STI care, condom promotion, and creating an enabling environment components, and Fung et al [ 36 ] evaluated a strategy that includes STI treatment, peer education and condom distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies evaluated a package of prevention or prevention and treatment interventions and around a third of the interventions integrated to the current health care system or programs on the ground (Additional file 3 ). For example, Dandona et al [ 35 ], evaluated a program consist of behaviour change, STI care, condom promotion, and creating an enabling environment components, and Fung et al [ 36 ] evaluated a strategy that includes STI treatment, peer education and condom distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The high cost-effectiveness of community mobilization and empowerment found is likely to be primarily due to the underlying cost-effectiveness of HIV prevention in India [20] , [22] , [54] . The low cost of HIV prevention in India [55] , together with a sizeable impact on the HIV epidemic [29] , means that community mobilization and empowerment, as an intertwined intervention that enhances the effectiveness of the HIV prevention, has a sound basis on which to yield substantial returns from an HIV perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The effect estimates from the causal pathway model for condom use at last sex with occasional clients (see Tables S1 and S2 in Appendix S1 ) were used to parameterise the fraction of increases in FSW condom use with clients associated with the CM and empowerment component of the intervention, and thus explore the impact of CM and empowerment activities on HIV infections averted using the simulated matched control groups described below. Unlike most previous exercises in modelling impact for cost-effectiveness analyses at scale in India [19] , [21] , [22] , the model used is dynamic (incorporating indirect population-level effects not captured in cohort models) and is employed within a Bayesian framework [1] , [29] to allow a better quantification of uncertainty.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study reported availability of second-line regimens will further increase survival, but their cost-effectiveness depends on their relative cost compared with first-line regimens [17]. Another study shows the point estimate for the cost per DALY saved from the averted HIV infections for all interventions was much lower than the per capita gross domestic product in Indian states[18]. Similarly, another study also estimated the cost of HIV prevention intervention for commercial sex workers and suggested the cost varied depending upon the scale (coverage and service volume indicators).…”
Section: Introductionmentioning
confidence: 99%